2008
DOI: 10.1111/j.1751-1097.2007.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐validation of Murine UV Signal Transduction Pathways in Human Skin

Abstract: Acute UVB irradiation of mouse skin results in activation of phospatidyinositol-3 (PI-3) kinase and mitogen-activated protein kinase (MAPK) pathways leading to altered protein phosphorylation and downstream transcription of genes. We determined whether activation of these pathways also occurs in human skin exposed to 4x minimal erythemic dose of UVB in 23 volunteers. Biopsies were taken prior to, at 30 min, 1 and 24 h post-UVB. In agreement with mouse studies, the earliest UV-induced changes in epidermis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 56 publications
5
23
0
Order By: Relevance
“…Cr(VI) exposure in BEAS-2B cells increased Stat3 activation and phosphorylation whereas treatment of luteolin suppressed them. MAPKs are made up of three family members that include extracellular-signal-related protein kinases (ERKs), stress-activated c-JUN N-terminal (JNKs/SAPs) and p38 kinases (Einspahr et al , 2008). Previous studies have shown that Cr(VI) markedly induces MAP kinase pathways in CL3 cells and is positively correlated with oxidative stress (Chuang et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Cr(VI) exposure in BEAS-2B cells increased Stat3 activation and phosphorylation whereas treatment of luteolin suppressed them. MAPKs are made up of three family members that include extracellular-signal-related protein kinases (ERKs), stress-activated c-JUN N-terminal (JNKs/SAPs) and p38 kinases (Einspahr et al , 2008). Previous studies have shown that Cr(VI) markedly induces MAP kinase pathways in CL3 cells and is positively correlated with oxidative stress (Chuang et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK are made up of three family members that include extracellular-signal-related protein kinases (ERKs), c-JUN N-terminal kinases stress-activated protein kinases (JNKs/SAPs) and p38 kinases (Einspahr et al , 2008). During the activation of p38MAPK, several upstream kinases, including MAP kinase kinases (MKK) are also involved.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, of particular interest are MAP kinase, PI3 kinase, p53, cyclic AMP response-element binding protein (CREB) and JNK pathways that result in the induction of expression of specific genes that can lead to skin cancer. Some of the same pathways have also been described to be activated in pterygium, suggesting a further similarity between the two processes [3,4,5,6,7]. Several reports have documented the effects of UV exposition primarily on human skin and then on normal and pathological cultured ocular surface cells [18,19,20].…”
Section: Introductionmentioning
confidence: 95%
“…Pterygia can vary from small, atrophic quiescent lesions to large, aggressive, rapidly growing fibrovascular lesions that can distort the corneal topography, and, in advanced cases, obscure the optical center of the cornea [1,2]. Both epithelial cells and fibroblasts obtained from pterygia show transformed cell-like features, with a documented faster growth in culture compared to normal conjunctiva, and share with transformed cells the activation of several pathways like p38/MAPK, p53, and PI3 kinase [3,4]. …”
Section: Introductionmentioning
confidence: 99%